Flipping Roles: Exploring the Impact of a Flipped Classroom Method on the Student Success Rate in a Pharmacology Course (International Journal of Studies in Nursing, 2019)
There are an estimated 1.05 million job postings across the United States for registered nurses by the year 2022. To answer for this demand, nursing programs across the nation are undertaking quality improvement initiatives to increase student success and graduation rates. Referencing Ausebel’s Assimilation Theory and motivated by the research question: Did the introduction of the active, flipped classroom make a difference in student success rates when compared to the student success rates in the traditional class room in a pharmacology course a retrospective data analysis was performed. The relationship between student success rates in the flipped classroom were compared to the relationship of student success rates in the traditional classroom based on the comprehensive final examination. There were 169 final examination scores extracted for data analysis 90 traditional classroom, 79 flipped classroom examination scores were extracted for data analysis. Independent t-tests were used to compare the means of the final examination scores in the traditional classroom to the means of the final examination scores in the flipped classroom. The findings of the research indicated there was no significant difference between the mean scores of the traditional classroom (M= 81.7, SD= 6.3) and the mean scores in the flipped classroom (M= 80.1, SD= 7.8, t(135)= 1.39, p= .15). Based on the results of this study, it is concluded that the flipped classroom can be utilized as an alternative method of instruction in the course as well as in other courses within the nursing program.